Pengaruh RGEC Terhadap Financial Distress Pada Bank Muamalat Indonesia - Alvidianita, Ayu; Rachmawati, Lucky (Jurnal Ekonomika dan Bisnis Islam, 2019)
Financial distress is a condition in which a company cannot generate revenue because it is unable to meet or cannot pay its financial obligations. In order for the banking company can overcome the condition of financial distress is required the existence of a judgment against the bank's health level using RGEC. This research aims to know the influence of NPF (credit risk), FDR (liquidity risk), the size of the Board of Commissioners (GCG), ROA (earning ratios), and CAR (Capital) against financial distress was measured using a model of Altman Z-score modification at PT Bank Muamalat Indonesia 2012-2016 Period. Analysis techniques are used multiple linear regression analysis. The results showed that the NPF, the size of the Board of Commissioners and the CAR do not affect significantly to financial distress in Bank Muamalat Indonesia 2012-2016 period. While FDR and ROA effect significantly to financial distress in Bank Muamalat Indonesia 2012-2016 period.